2023
DOI: 10.1111/bjh.19108
|View full text |Cite
|
Sign up to set email alerts
|

Potential for a large‐scale newborn screening strategy for sickle cell disease in Mali: A comparative diagnostic performance study of two rapid diagnostic tests (SickleScan® and HemotypeSC®) on cord blood

Aldiouma Guindo,
Zenab Cisse,
Ibrahima Keita
et al.

Abstract: SummarySickle cell disease (SCD) is a life‐threatening disease requiring reliable early diagnosis. We assessed the acceptability and diagnostic performances of two rapid diagnostic tests (RDTs) to identify SCD (HbSS, HbSC, HbS/β‐thalassaemia) or SCD carrier (HbS/HbC) in a pilot SCD newborn screening (NBS) strategy in Mali. All consenting delivering women were offered SCD NBS using cord blood sampling on two RDTs (SickleScan® and HemotypeSC®) compared to the high‐performance liquid chromatography (HPLC) gold st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The HemoTypeSC TM POC test kit, which only requires capillary blood samples and unfiltered tap water, was tested over a 2-year period in Koutiala hospital in rural Mali and found to be satisfactory for NBS [ 1530 ]. Similarly, the acceptability and diagnosis performances of two POC tests (SickleScan ® and H HemoTypeSC TM ) were evaluated against HPLC methodology in three maternity hospitals in Mali (two urban clinics in Bamako and one rural clinic in Kayes) using cord blood, and both tests were found to be acceptable NBS tests [ 1531 ]. A study of the Emmel test routinely used to test adults for SCA was found to be severely lacking when used for screening newborns in Bamako, and its use was NOT recommended despite its low cost and relative simplicity [ 1532 ].…”
Section: Resultsmentioning
confidence: 99%
“…The HemoTypeSC TM POC test kit, which only requires capillary blood samples and unfiltered tap water, was tested over a 2-year period in Koutiala hospital in rural Mali and found to be satisfactory for NBS [ 1530 ]. Similarly, the acceptability and diagnosis performances of two POC tests (SickleScan ® and H HemoTypeSC TM ) were evaluated against HPLC methodology in three maternity hospitals in Mali (two urban clinics in Bamako and one rural clinic in Kayes) using cord blood, and both tests were found to be acceptable NBS tests [ 1531 ]. A study of the Emmel test routinely used to test adults for SCA was found to be severely lacking when used for screening newborns in Bamako, and its use was NOT recommended despite its low cost and relative simplicity [ 1532 ].…”
Section: Resultsmentioning
confidence: 99%